PECULIARITIES OF PUBLIC ELECTRIC TRANSPORT DEVELOPMENT IN SOME UKRAINIAN CITIES (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2021)
Analysis of the development of trolleybus transport in Ukrainian regional centers (Zhytomyr, Rivne, Ternopil, Chernihiv, the largest city in terms of population of Kyiv region - Bila Tserkva) was conducted. A comparison of these cities in terms of their area, population, population density in cities, the number of bus and trolleybus routes, the length of the catenary and the number of trolleybuses was carried out. The characteristic features of trolleybus routes of cities are analyzed and noted and the strategy of their further improvement and renewal of rolling stock is revealed. The peculiarity of the route network in Zhytomyr is noted, which consists in the presence of a ring route, which allows to connect the areas far from the city center.It is shown that the peculiarity of the contact network of Rivne is its exit from the geographical boundaries of the city, which is justified by the large flow of passengers on working days of the week, who move to the Rivne plant of high-voltage equipment. It is noted that the AKSM 43303A double-decker bus and 12 Dnipro T203 trolleybuses with autonomous running were put into operation.From the analysis of schemes, features of trolleybus routes, the existing fleet of trolleybuses and their service life in these cities, it is concluded that in the cities of Ukraine with these characteristics are dominated by trolleybus networks of radial location with the ability to combine suburbs. The best solution for choosing a trolleybus contact network in such cities is to choose radial routes from the center to the peripheral areas of the city in combination with circular routes connecting the main streets. The fleet of trolleybuses is outdated, they have been in operation for 20-40 years, so it needs more active renewal. The best in terms of age composition of trolleybus parks of the cities analyzed, as of 01.01.2020, is the park of Chernihiv, the worst - the city of Rivne.Key words: urban passenger transportation, electric transport, trolleybus, route network, contact network, environment